2013
DOI: 10.1039/c3nr00185g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically induced actuation of liquid metal marbles

Abstract: Controlled actuation of soft objects with functional surfaces in aqueous environments presents opportunities for liquid phase electronics, novel assembled super-structures and unusual mechanical properties. We show the extraordinary electrochemically induced actuation of liquid metal droplets coated with nanoparticles, so-called "liquid metal marbles". We demonstrate that nanoparticle coatings of these marbles offer an extra dimension for affecting the bipolar electrochemically induced actuation. The nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
210
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 35 publications
0
210
2
1
Order By: Relevance
“…We next observe that the coalesced drop shifts toward the grounded gate, which in this case is acting as the cathode (Figure 3b,c). This is, again, in contrast to what is typically seen in continuous electrowetting, during which EGaIn droplets in an NaOH solution move toward the anode 32, 33. Thus, we conclude that bipolar electrochemistry and oxidation must be the driving factor in our experiments.…”
Section: Resultsmentioning
confidence: 58%
“…We next observe that the coalesced drop shifts toward the grounded gate, which in this case is acting as the cathode (Figure 3b,c). This is, again, in contrast to what is typically seen in continuous electrowetting, during which EGaIn droplets in an NaOH solution move toward the anode 32, 33. Thus, we conclude that bipolar electrochemistry and oxidation must be the driving factor in our experiments.…”
Section: Resultsmentioning
confidence: 58%
“…1, the pressure difference Δp is positive, indicating that the downstream hemisphere of the droplet pushes the surrounding liquid harder and produces a force to drive the droplet toward the upstream (26). However, unlike (26), in this case, when the motion of the droplet is ceased by the neck of the chamber, the pressure difference across the droplet causes the flow of the surrounding liquid along the channel and thus converts the applied electric potential directly into mechanical movement of the liquid (detailed explanation is given in SI Appendix, section 2). Theoretically, the pressure difference exists continuously along the surface of the Galinstan droplet as long as the electric field is applied, and the principle for the resulting flow motion is called continuous electrowetting, which is an electrical analog to the Marangoni effect (4,26,27).…”
Section: Significancementioning
confidence: 99%
“…We also show that the system operates with other electrolytes, including neutral sodium chloride (NaCl) and Phosphate-buffered saline (PBS) solutions. However, the system does not operate with acidic electrolytes of pH less than 6.5, as we have previously demonstrated that Galinstan droplets in acidic solutions are weakly affected by electrowetting (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the search for safe‐handling room‐temperature LMs only narrows down to gallium‐based LMs, a group of alloys consisting gallium and other metals like indium, tin, etc. Recently, self‐powered motor,11 jumper,12 oscillator,13 soft actuators,14, 15, 16 and 2D semiconductor skin17 demonstrated with this class of material shed light on their new possibilities toward more diverse applications. Here, we report a particle‐eating phenomenon of gallium‐based LMs, which mimics the biological phagocytosis process (also known as cellular‐eating, a basic cell behavior referring to the transportation of external particles into cells from across the membranes18, 19, 20, 21), and thus we call it LM‐Phagocytosis.…”
mentioning
confidence: 99%